PALESTINIAN UNIVERSITY ENGLISH PROFESSORS AND STUDENTS' PERSPECTIVES OF ONLINE LEARNING DURING COVID-19 PANDEMIC - Heba Khalil Jadallah; Mohammed A A Farrah (Universitas Kuningan, 2022)
COVID-19 is a virus that affects all spheres of life all around the world. Students and instructors all around the world are forced to transfer to online learning applications as a substitute for face to face learning. Hence, the pandemic has disrupted the Palestinian educational system and caused online learning to become a necessity. This study observes Palestinian university student and instructor perceptions toward using online learning applications during the COVID-19 pandemic. Quantitative and qualitative tools were used to collect data from students and instructors from 12 Palestinian universities. Thus, to collect data the researchers distributed 2 online questionnaires and conducted 32 semi-structured interviews. The sample of this study consisted of 375 students and instructors from different Palestinian universities. The results show that both students and instructors agree that online learning has advantages such facilitating learning at any time and place. Still, online learning has more disadvantages such as internet interruption, poor interaction, and more. Instructors and students both harbor negative attitudes toward using online applications. Finally, the study concluded with recommendations to improve online learning in the future. To facilitate higher quality online learning, instructors and students need support, training and a well-developed infrastructure. Keywords: advantages; challenges; online learning; Palestinian Universities; solutions.